1996
DOI: 10.1021/ma951471m
|View full text |Cite
|
Sign up to set email alerts
|

The Pivotal Role of Excess Nitroxide Radical in Living Free Radical Polymerizations with Narrow Polydispersity

Abstract: The pivotal role of the nitroxide concentration in bulk living polymerization of styrene was studied between 115 and 135 °C, using in situ electron spin resonance spectroscopy (ESR) to follow the concentration of the TEMPO stable free radical during the polymerization. Molecular weight and conversion were also followed on the same reaction mixtures using gel permeation chromatography and thermogravimetric analysis, respectively. While molecular weights were linear with conversion, to high conversion, there was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
148
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(161 citation statements)
references
References 24 publications
10
148
1
Order By: Relevance
“…16 Then DCDPS was synthesized by an oxidative coupling reaction of ethyl ␣-cyanophenylacetate with a Cu ϩϩ -TMEDA-O 2 system in chloroform. 17 Namely, in a 250-mL three-necked flash equipped with a magnetic stirrer bar, an oxygen buret and a reflux condenser were placed 9.0 g (47.6 mmol) of ethyl ␣-cyanophenylacetate in 150 mL of chloroform, 5.0 g (50.5 mmol) of CuCl and 6.0 mL (50.5 mmol) TMEDA (as catalyst), and 7.0 g of MgSO 4 (to remove water). At 50°C, the whole system was then flushed and filled with oxygen.…”
Section: Preparation Of Dcdps Thermal Inifertermentioning
confidence: 99%
See 1 more Smart Citation
“…16 Then DCDPS was synthesized by an oxidative coupling reaction of ethyl ␣-cyanophenylacetate with a Cu ϩϩ -TMEDA-O 2 system in chloroform. 17 Namely, in a 250-mL three-necked flash equipped with a magnetic stirrer bar, an oxygen buret and a reflux condenser were placed 9.0 g (47.6 mmol) of ethyl ␣-cyanophenylacetate in 150 mL of chloroform, 5.0 g (50.5 mmol) of CuCl and 6.0 mL (50.5 mmol) TMEDA (as catalyst), and 7.0 g of MgSO 4 (to remove water). At 50°C, the whole system was then flushed and filled with oxygen.…”
Section: Preparation Of Dcdps Thermal Inifertermentioning
confidence: 99%
“…In 1995 Matyjaszewski 2 and Sawamoto 3 discovered a new system, halocompound/transition metal/organic ligand, for living radical polymerization of several vinyl monomers, that is, atom transfer radical polymerization (ATRP), which appears to be the most versatile approach to controlled radical polymerization. Another attractive approach is nitroxyl-mediated polymerization, 4 which enables good control of the polymerization of styrene, but it is not so efficient for (meth)acrylate monomers. Also, Otsu and his coworkers 5 reported that iniferters (initiator-transfer agent-terminators) can be used for "living" radical polymerization of vinyl monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the capture rate constant k c , the kinetics of nitroxide radical trapping, including solvent effects as well as structural effects, have been studied by Beeckwith et al 18,19) and Ingold et al 20) , and the rate constant k c appeared to be lower than the diffusion-controlled limit. In the scope of macromolecular alkoxyamines, Veregin et al 21) have studied the bulk polymerization of styrene with Tempo as counter radical and benzoyl peroxide as initiator. They have reported a value of K = 3.4 6 10 -11 mol N L -1 at 125 8C, with an activation energy E a = 77.5 kJ N mol -1 , for the equilibrium involving polystyryl radical and Tempo.…”
Section: Introductionmentioning
confidence: 99%
“…Some works state that improved ef®ciency requires excess of initiator, 12 while others claim that the nitroxide must be in excess for better results. 13 The results obtained from the LC monomer homopolymerization indicate that both situations and equimolar amounts of initiator and nitroxide can be successfully used if the ratio between them is near unity.…”
Section: Methodsmentioning
confidence: 98%
“…GPC fractionating gave an LC homopolymer and a block copolymer fraction in a proportion of 1:5. The block copolymer fraction 13 C NMR spectrum showed the presence of a peak at 42 ppm, which was assigned to the CH 3 ÐN present in the thiuram end-groups. The composition was determined from the 1 H NMR spectrum, which showed a molar ratio between polystyrene and LC segments of 1:9.…”
Section: Methodsmentioning
confidence: 99%